Cacería de brujas en Coahuila, 1748-1751. "De Villa en villa, sin Dios ni Santa María" - Semboloni, Lara (El Colegio de México, A.C., 2004)
By reviewing the myths of witchcraft and sorcery, this paper analyzes the actors and social practices in a frontier  town, the last bulwark  before  total  wilderness,  in  the  Northern state of Coahuila,  Mexico. The author  studies the process of Inquisition during  1748-1751, a period  when  people  were accused of and tried  for diabolic  activities. The trials reveal a tendency  to explain the  game of human  passions  within  an unknown reality —characterized  by   an   apparent   lack   of   logic   and   formal canons—  through supernatural activities  and  satanic  pacts  atributed to  women,  regardless  of social class. In  this  context, moral  —and  political—  authorities  tried  to  stop  promiscuity, and their actions were seen as a need and determination to control a very fluid social structure,  i.e., to establish norms  for the regulation of moral standards  and collective values.